Hydroisomerization–cracking of n-octane on Pt/WO42−–ZrO2 and Pt/SO42−–ZrO2: Effect of Pt load on catalyst performance - Grau, Javier Mario (2001)
The hydroconversion (isomerization–cracking) of n-octane was studied at 300°C, 1.5 MPa, WHSV=4 and H2/nC8=6 using oxoanion promoted zirconia with different Pt concentrations (0.1, 0.5 and 1%) as catalysts. Tungstate was added to zirconia by impregnation with ammonium meta-tungstate or tungstic acid solutions and calcined at 800°C. Sulfate was added by impregnation with 2N H2SO4 and calcined at 620°C. Isooctanes are intermediate products that are cracked to C3–C5 alkanes with predominance of isoalkanes. Sulfate zirconia is the most active and selective catalyst to cracking products. The addition of 0.1% of Pt produces an increase in activity and stability, respect of the support without metal. However, the increase in Pt content (0.5 and 1.0%) produces a decrease in nC8 conversion and in cracking products. The metallic properties of Pt are decreased by its strong interaction with the support, mainly with sulfate zirconia; at the same time, Pt decreases the acid cracking activity of the support.